Create Sustainable Competitive Advantage through Environmentally Friendly Culture of Village Credit Institutions - GEDE SADIARTHA, Anak Agung Ngurah (Journal of Environmental Management and Tourism, 2019)
The purpose of this research is to obtain empirical The Village Credit Institutions "Lembaga Perkreditan Desa" (herein after abbreviated to as Village Credit Institution)‟ in Bali has a unique organizational culture. It owned by traditional villages in Bali are able to compete with other modern banking. This scientific work discusses sustainable competitive advantage management and the values of the organizational culture that strengthens of Village Credit Institution get the trust of the people of Bali, able to compete with modern banking institutions. The result of the research shows that a sustainable competitive advantage management strategy coupled with the awig-awig strength in the Village Credit Institution as a medium for the role of community discipline, pade ngelahang's attitude is able to build the confidence of local villagers and the strength of the human resource role in menyame braye as an effort to build shared values.